Development of Social and Environmental Competences of Teachers in Training Using Sound and Visual Landscape - Amparo Hurtado Soler; Ana María Botella Nicolás; Rafael Fernández Maximiano; Silvia Martínez Gallego (MDPI AG, 2023)
The soundscape was used as the basis of the research carried out by the Teaching Faculty of the Universitat de València Spain. The research focused on two aspects: (i) study the relationship between environmental sounds and emotions as a base to promote environmental awareness; and (ii) analyze the usefulness as an educational resource for the development of social and environmental competences of teachers in training. Thus, a didactic sequence was designed using 360º virtual recordings of natural and human landscapes in which participants described sound and visual elements that they associated with a range of emotions. Moreover, participants identified environmental problems and reflected on the usefulness of the sound and visual landscape in the acquisition of social and environmental competences. Both qualitative and quantitative methods were used in this study and 327 teachers participated in the training. The findings show the observation of sound and visual elements can facilitate the understanding of environmental problems. The natural soundscape was associated with positive emotions, while more industrial or urban landscapes were associated with negative emotions. This can affect on people's well-being. Moreover, the participants had a good perception of the development of their social and environmental competences, and considered that the activity promoted the transfer of knowledge and developed argumentative and critical capacities. This approach offers the opportunity to create learning environments contextualized in the landscape that facilitate the connection of scientific and artistic disciplines from an experiential perspective. It is essential to continue studying and implementing educational strategies that promote the integration of theory and practice.